Computer aided flow analysis in a cavitation tunnel / Tengku Maziah Tengku Abdullah - Tengku Abdullah, Tengku Maziah (Faculty of Mechanical Engineering, Universiti Teknologi MARA, 1998)
This report presents the Computer Aided study of the flow conditions in a Cavitation Tunnel using the CFD software ‘FLUENT’. A computer model of a Cavitation Tunnel is made and flow analysis are presented.The suitable geometry of the Cavitation Tunnel is found using different models and the exact location in which propeller specimens can be studied are identified. Suitable value of the velocity at the pumping zone is found using the number of trials on the computer model.